Komunikasi Interkultural dan Pluralitas Toleransi Antar Umat Beragama - Yasyva Agfa Nizar; Yusnia I'anatur Rofiqoh (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2021)
This This paper attempts to describe the effectiveness of intercultural communication in building plurality of thoughts and attitudes of tolerance among religious communities, and provides an overview of the concept of intercultual communication and the concept of plurality of tolerance of religious communities. This study is a literature study through the work of other researchers obtained through journals, books, and the internet. The results of the study show that the concept of intercultural communication has a relationship in building perceptions, attitudes and actions of society in carrying out life activities in a socio-religious context. communication becomes a medium in forging bonds between religious communities. Integration between tolerance and plurality is constructed in a system of religious harmony and harmony based on human attitudes in communication, including several attitudes shown when individuals attend and internalize external events including denial, defense, minimization, acceptance, adaptation and integration. This process will certainly be faced by each individual with various attitude criteria that are shown including being exclusive, inclusive and pluralist. Thus tolerance comes with effective and efficient communication and provides a positive view of each ethnic, racial, cultural and religious entity.